Investment opportunities in the source country and temporary migration - Slobodan Djajic (Graduate Institute of International and Development Studies, 2009)
This paper examines how attractive investment opportunities available to temporary migrants in their country of origin affect their saving behavior and the optimal duration of stay abroad. The model predicts an inverse U-shaped relationship between migration duration and the expected rate of return on repatriated savings. A higher rate provides an incentive to go back earlier and consume less abroad, while it can also trigger emigration aimed at generating the savings required for investment after return. At a more general level, the paper illustrates how the behavior of temporary migrants reflects the interaction between their preferences and the opportunities available in the labor and capital markets of both countries.
Keywords: F22; 330; International migration; Remittances; Return migration; Internationale Wanderung; Dauer; Sparen; Rücküberweisungen; Kapitaleinkommen; Theorie